Pengaruh Model Example Non Example Terhadap Kemampuan Pemahaman Konsep Bangun Datar pada Siswa Kelas IV di Sekolah Dasar - Ayu Fitri (LPPM Universitas Buana Perjungan Karawang, 2020)
This research is motivated by the learning of mathematics is the low absorption and understanding of students towards mathematical concepts, student involvement in learning mathematics is not optimal, students are still preoccupied with their own world by not paying attention to the explanation of the material provided by the teacher. This research method uses a quantitative approach. The population used was grade IV students of SDN Kertasari I, the sample in this study was class IVA as an experiment and class IVB as a control class. The results of this study class IV A (experimental class) obtained an average of 81.833 with a variance of 153.316 and a standard deviation of 12.382. Whereas the IVB class (Control class) obtained an average of 74,031 with a variance of 198,096 and a standard deviation of 14,075. So that there is an influence of the Non Non Example learning model on the ability to understand the mathematical concepts of students in the SD Negeri Kertasari 1 class. This is evidenced by the results of the t-test obtained = 2,311 and 2,000.